WITHDRAWN—Administrative Duplicate Publication: 'I am more than my IQ': Analysis of the experience of a gifted learner. (September 2019) - Brandisauskiene, Agne
Brandisauskiene A (2019) 'I am more than my IQ': Analysis of the experience of a gifted learner. Gifted Education International . Epub ahead of print 24 April 2019. Ahead of Print article withdrawn by publisher. Due to an administrative error, this article was accidentally published twice Online First with different DOIs. The correct and citable version of the article remains: Brandisauskiene A (2019) 'I am more than my IQ': Analysis of the experience of a gifted learner. Gifted Education International . Epub ahead of print 11 April 2019. DOI:10.1177/0261429419840648